Pelatih pencatatan Keuangan Sederhana Dengan Mengunakan Aplikasi Money Mgr Pada UMKM Kebab Palupy Nusa Indah - Agustin, Revalinda; Abi, Yudi Irawan; Rahman, Abdul; Yulyanti, Oni; Harwini, Dewi (Jurnal Dehasen Mengabdi, 2025)
Financial recording is often an obstacle for MSME players, including Arabian Kebab palupy in Bengkulu City. This community service activity aims to increase the financial management capacity of these MSMEs through the application of technology based on the Money Manager (Money Mgr) application. The method used includes preparation, training, and evaluation of digital business financial records. In today's digital era, there are still many MSMEs that still use manual records, especially in the Bengkulu city area. one of the umkm that still uses manual records is kebab palupi which is located in Nusa indah, Bengkulu city. Financial management is very important, therefore we recommend a practical and regular application for financial management or financial records, one of which is the Money Mgr application. We serve the community, namely SMEs to recommend or teach the community to use the Money Mgr application. therefore, we the Devotion Team provide technology-based financial recording training, especially for recording income and expenses which will result in good and neat bookkeeping. The method used is lecture in the form of interviews to the manager of the Bang Aji Kebab MSME. The results of the service are very helpful for the manager of the Kebab palupy MSME in recording financial books.